3 D scanner integration with product development - Kumar, Lalit; Shuaib, Mohd; Tanveer, Qamar; Kumar, Vineet; Javaid, Mohd; Haleem, Abid (International Journal of Engineering and Technology, 2018)
Purpose: The purpose of this paper is to give a basic understanding of the working and use of 3 D Scanner in reverse engineering, shape reconstruction and product designing. It discusses the use of 3 D Scanner in product development field and also presents a method to acquire the required data of existing component through which we can develop the new product.Design/methodology/approach: To understand the fundamental working principle of the scanner, an algorithm is discussed which shows the data collection procedure of the scanner. The obtained data is verified with existing CAD data with the help of software, and an example is also discussed to explain the process.Findings: This study shows that the integration of scanner technology with product development cycle will help to improve the development process of any product, as this technology provides benefits through reduction in time, money and resources.Research limitations/implications: The speed and accuracy of the Scanner depends upon the method adopted to capture the data.Practical implications â€“ Reverse engineering is a process of change an existing product into a new product. Development of an existing product we required the three-dimensional data of the product. The data acquisition process is critical and time-consuming. The design expert uses different approaches to collect the necessary parameters. This study discusses one of the data acquisition technology, i.e. 3-dimensional scanner.Originality/value â€“ In this article, we are discussing one of the original methods to show the integration of scanner technology with product development.Â
Keywords: 3 D Scanner; Data Acquisition; Product Designing; Product Development; Product Redesigning; Reverse Engineering; Scanner Algorithm.